Analysis of Micro, Small, and Medium Enterprises (MSMEs) Governance as Supporters of the Gunung Kelud Tourism Area (A Case Study of Kelud Honey Pineapple Traders, Kediri Regency) - Hermawan, Romy (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2024)
Sugihwaras Village is a village located in Ngancar Subdistrict, Kediri Regency. A well-known agricultural commodity is pineapple with a typical mainstay product, namely